Burden of Skin Diseases at a Tertiary Care Hospital - Tameez ud din , Tameez ud din; Abdul Qudus Butt, Abdul Qudus Butt; Fatima Ali Bangash, Fatima Ali Bangash; Hina Abbas, Hina Abbas (Journal of Rawalpindi Medical College, 2010)
Background: To estimate frequencies of skin diseases in a tertiary care hospital catering to patients from Rawalpindi and the suburbs. Methods: In this comparative cross sectional study a total of 41947 patients were evaluated and divided into four major groups, Allergic, Infectious, Inflammatory and Autoimmune and a fifth Miscellaneous group. From the medical records, history, physical examination and whenever necessary, laboratory investigations were analyzed. Results: The most common infectious skin disorder was Scabies accounting for 18.9% of the total skin diseases. Most common allergic disorder was Dermatitis that accounted for 13.9% of the cases. Acne being the most common inflammatory condition constituted 11.96% of the cases. The most commonly affected age group was between 21-30 years with 19.5% of the cases. A seasonal pattern was seen and the maximum number of patient visits were seen in June (4272 cases) followed by July (4196 cases) and August (4146 cases). Conclusion: The data suggests that the disease burden in Rawalpindi and the suburbs has been underestimated. These are more than benign diseases and special consideration needs to be given to extended public health initiatives to improve their control.